National minorities/ New minorities. What similarities and differences in contemporary Europe? - Plasseraud, Yves (Sens public)

(untitled) (Département des littératures de langue française, 2010)
The Minorities question is currently a hot issue in Europe. But what are the concerned minorities and to which of them should the existing – national and international – legal instruments apply? Amongst the States of the New Europe, Latvia, with its important immigrant population, offers a striking example of the current minority problematics. The study of this Baltic country reveals the main issues about this question and shows why there are currently reasons to broaden the traditional concept of national minorities. I also shows how some countries have undertaken to instrumentalize this trend to turn “their” minorities in neighbouring states into political instruments.